Gradiente pluviométrico en el macizo del Moncayo (Zaragoza y Soria) - Del Valle, Javier; San Román, Javier (Geographicalia, 2017)
We shows the the rainfall and altitude correlation in the N and S slopes of Moncayo's mountain, we have used the best observatories, according to their nearness, and the most suitable kind of adjustment. We pretend to estimate the anual average rainfall in this mountanious area and to elaborate the correspondent map.
Keywords: Moncayo; rainfall and altitude correlation; rainfall map.